Romani Studies in Latin America and Caribbean: Perspectives and Challenges - Fotta, Martin; Sabino-Salazar, Mariana (Romano džaniben, 2021)
The article attempts to fill the gap in knowledge about Roma in Latin America and the Caribean (LAC), offering an overview of the key issues related to the Romani populations in LAC and the variety of their groups, histories, denominations, statuses, recognition etc., including an overview of the state of the arts in Romani studies in LAC. The authors summarize the texts included in the thematic double issue of the Romano džaniben journal and the information from a questionnaire which they distributed among 57 Romani studies researchers in LAC. Based on these observations they they challenges the euro-centric view so far dominating the Romani studies as a discipline and argue for the neccessity of including the Transatlantic perspective.